Fatores associados à ocorrência de arboviroses em municípios de Mato Grosso - Cruz, Lucinéia Claudia de Toni Aquino da (2020)
The changes in social and environmental conditions contribute to the persistence of diseases such as arboviruses, causing global health problems. Controlling the vector- borne diseases’ burden is one of the greatest challenges facing public health today. One of the alternatives is developing studies with an integrated strategy in local scenarios, presenting a differentiated ecology. In this context, this paper aimed at analyzing factors that condition the arboviruses occurrence, such as socioenvironmental characteristics and level of knowledge for vector control in four Municipalities of Mato Grosso, Brazil. For this reason, the cities of Cáceres, Cuiabá, Rondonópolis and Sinop were chosen for epidemiological reasons. Data indicated these regions at risk for vectors’ proliferation. The collection period was from February 2017 to January 2018, in six neighborhoods of each municipality, according to the preset sampling process. 19,110 mosquitoes were collected; 16.58 (83%) of Culex quinquefasciatus (44% females and 56% males), 2,483 were Aedes aegypti (54% females and 46% males); other genera such as Psorophora, Anopheles, Coquelitidae, and Sabethes corresponded to 0.25 % of samples. From the total mosquitoes captured, 261 pools of females were formed, with similar characteristics to be subjected to viral analysis and genetic sequencing. Among these pools, 51 were positive for arboviruses such as DENV2, DENV4, ZIKAV, CHIKV, MAYV, and OROV. Some samples with nucleotide sequencing showed the Oropouche virus in C. quinquefasciatus with 100% similarity to other samples in the state. Correlations were established between mosquitoes and climatic variables, highlighting the dew-point temperature (P-value, 0.000) for all mosquito species and wind speed (females P- value<=0.007 and males P-value<0.004). Regarding the socioeconomic variables on municipalities, with aspects directly linked to basic sanitation and infrastructure, correlations occurred between education, income and garbage collection with the vectors’ presence. Taking into account that the level of knowledge, attitudes and prevention practices can also interfere in diseases occurrence, a CAP-type questionnaire was applied to the ACE (Endemic Combat Agents). Associations were observed between knowledge, age group, education and length of service. Our work in Mato Grosso demonstrated different patterns in the urban space organization, exerting a direct influence on the microclimate and the vectors’ presence. However, the arboviruses’ transmission dynamics, in general, is similar, despite the structural and environmental changes observed over time.